(untitled) (European Journal of Pure and Applied Mathematics, 2022)
In this paper, we define the concepts of alomst bi-interior ideal and fuzzy almost bi-interior ideal in semigroups. Moreover, we prove that relation between almost bi interior ideal and fuzzy almost bi-interior ideal.